Types And Measurement Of Poverty in Australia - Adi, Isbandi Rukminto (UI Scholars Hub, 2008)
During Millennium Summit 2000 the United Nations (UN) has declared the Millennium Development Goals. The UN acknowledges the importance of poverty problems. The first goal of MDGs is to eradicate extreme poverty and hunger The declaration also mentioned that proportion of people whose income is less than one dollar a day and people who suffer from hunger should decrease by half in 25 years (from 1990 to 2015) Related to poverty problems The 8th goal of MDGs is to develop a global partnership for development Global Partnership, in this case, could be seen by giving opportunities for people from developing countries to learn about the nature of poverty and the policy and programmes related to poverty reduction that have been developed the developed countries. In this case, the developed country which will be described is Australia as one of the neighbouring countries which has achieved highest standard of human development. In relation to that matter, therefore this article will focus on describing the nature of poverty in Australia and how to measure poverty which covers the needs of the community From the Australian's experience, the author hope there will be a lesson learned could be developed by the Indonesian's